Changes in laboratory markers of thrombotic risk early in the first trimester of pregnancy may be linked to an increase in estradiol and progesterone. Issue 178 (June 2019) - Bagot, C.N.; Leishman, E.; Onyiaodike, C.C.; Jordan, F.; Gibson, V.B.; Freeman, D.J.
Abstract: Background: Pregnant women are at increased risk of venous thrombosis compared to non-pregnant women. Epidemiological and laboratory data suggest that hypercoagulability begins in the first trimester but it is unknown exactly how early in pregnancy this develops. The mechanisms that result in a prothrombotic state may involve oestrogens and progestogens. Methods: Plasma samples were taken prior to conception and five times in early pregnancy, up to Day 59 gestation, from 22 women undergoing natural cycle in vitro fertilization, who subsequently gave birth at term following a normal pregnancy. Thrombin generation, free Protein S, Ddimer, Fibrinogen, factor VIII, estradiol and progesterone were measured. To counter inter-individual variability, the change in laboratory measurements between the pre-pregnant and pregnant state were measured over time. Results: Peak thrombin, Endogenous Thrombin Potential, Velocity Index and fibrinogen significantly increased, and free Protein S significantly decreased, from pre-pregnancy levels, by 32 days gestation. Ddimer and VIII significantly increased from pre-pregnancy levels by 59 days gestation. Estradiol significantly increased by Day 32 gestation with a non-significant increase of 67% by Day 24 gestation. Progesterone significantly increased by Day 32 gestation. Almost all laboratory markers of thrombosis correlated significantly with estradiol and progesterone. Conclusion: Our work is the first to demonstrate that the prothrombotic state develops very early in the first trimester. Laboratory markers of hypercoagulability correlate significantly with estradiol and progesterone suggesting these are linked to the prothrombotic state of pregnancy. Clinicians should consider commencing thromboprophylaxis early in the first trimester in women at high thrombotic risk. Highlights: It is unclear how early in pregnancy women become hypercoagulable This study measured markers of hypercoagulability during very early pregnancy Laboratory hypercoagulability begins to develop during the fifth week of pregnancy Estradiol and progesterone may be linked to the prothrombotic state of pregnancy Consider starting thromboprophylaxis very early in high risk pregnant women